Lifelong learning in the AI era: opportunities and challenges for global learners - Mohd Ali, Siti Nur Dina; Ismail, Mohd Hafizul (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The rise of artificial intelligence (AI) is transforming education and promoting lifelong learning by providing personalised, flexible, and globally connected learning opportunities (Candy, 2002; UNESCO, 2021). AI tools, such as adaptive learning systems, ChatGPT, Grammarly, and Quillbot, support language learning, offer real-time feedback, foster self-directed learning, and enhance inclusivity for learners from diverse backgrounds (Ali & Ismail, 2025; Luckin et al., 2016). Additionally, AI skills improve employability as automation reshapes the workforce, with 50% of employees expected to need reskilling by 2025 (World Economic Forum, 2020). However, challenges like the digital divide limit access for learners in under-resourced areas, highlighting the need to address inequalities (van Dijk, 2020).